(untitled) (Journal of Educational Sciences, 2016)
Now the problem of formation of high qualification scientific staff of new formation on the basis of integration of education, science and the innovations corresponding both to the basic principles of Bologna Process and intellectual requirements and strategy of development of the republic is actual. Due to the transition to the international level of training, Kazakhstan accepted a new system of training «Bachelor – Master – PhD». By the present moment educational programs on each step of the higher and postgraduate education are improved. By preparation of scientific staff it is necessary to rely on experience of the developed foreign countries and to define possibility of applicability of structure of the program of development and improvement of young scientific prestigious universities according to requirements of economy, scientific, scientific-technical and innovative development of our country. Studying experience of the developed countries, there is a need of introduction of a following step for preparation of scientific staff of our country – post-doctoral studies. In the table of article educational and scientific degree of the former Soviet republics, Kazakhstan and the countries of the West. As can be seen from the table, Kazakhstan is currently at intermediate stages of the transition process of the educational system at the international level training.